Cases on Competitive Analysis of Selected Corporate Foundations in Malaysia - Ishak, Ismail; Hasnah, Haron; Mohd Hanafiah, Ahmad; Daing Nasir, Ibrahim; Mohd Ridzuan, Darun (IIUM Press, 2018)
There are many foundations formed in Malaysia. However, there are cases of success and failures. Therefore, this case study focuses on exploring the strategies used in the successful foundations and how they overcome obstacles to achieve their objectives. This study used a qualitative design that involved content analysis and interviews with the Chief Executive Officer and officers in charge of the foundations. Four foundations were selected for this purpose. The practices of the foundations were examined and comparisons were made between the foundations chosen. From this research, it is found that all four corporate foundations have fewer similarities but more differences in terms of operations. Findings from this study can be lessons learnt to other foundations on how the corporate foundations manage their organization, talents, challenges, and programs.